The impact of the Europeun Union grant on access to credit and production in smallholder sugarcane agriculture in Siphofaneni eSwatini - Machethe, Charles Lepepeule (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2019.